Cat Care and Services Booking Management System - Mohamad Hassan, Raihana Puteri; Mohd Safar, Noor Zuraidin (Applied Information Technology And Computer Science, 2025)
The Cat Care and Services Booking Management System was developed to overcome inefficiencies in manual booking processes at Cats Capsule. Issues such as overlapping bookings, miscalculated charges, and data loss were addressed by creating a web-based platform with features like user and cat profile management, booking and payment modules, calendar scheduling, and review submission. Developed using PHP and MySQL in a XAMPP environment, the system supports responsiveness and accessibility. Agile methodology enabled iterative development with regular feedback. Functionality testing confirmed that all modules met the requirements. The system improves administrative workflows, reduces errors, and enhances customer satisfaction through real-time slot viewing, email notifications, and better service evaluation. Overall, it provides a reliable and efficient solution for both customers and administrators.